Ольвійський декрет на честь калхедонця і деякі питання ольвійсько-калхедонських взаємовідносин - Русяєва, A.C.; Одрін, O.B. (Археологія, 2003)
У статті розглянуто новий проксенічний декрет з Ольвії на честь невідомого по імені жителя Капхедона. Роль цього міста у торговельних відносинах Ольвії з містами Середземномор'я визначається його стратегічно важливим географічним розташуванням. Важный источник для исследования торгово-экономических взаимоотношений Ольвии с разными античными городами представляют собой проксении. Фрагмент одной из последних проксений найден при раскопках святилища Аполлона Истроса в Западном теменосе Ольвии. По сохранившейся части надписи можно восстановить, что она была предоставлена жителю Калхедона и его потомкам, получавших в Ольвии не только собственно прокссению, но и подитию, ателию, а также свободный беспошлинный ввоз и вывоз товаров как в мирное, так и в военное время во второй половине IV в. до н. э. По другим источникам известно, что в III в. до н. э. неизвестный но имени ольвиополит получил проксению в Калхедоне. Этот город, расположенный возле узкого пролива Боспор Фракийский, играл важную роль в торговой деятельности Ольвии с греческими юродами Эгсиды в эллинистическое время. Авторы рассматривают возможные варианты торговых ольвийско-калхедонских связей, поскольку сами проксении не дают конкретных данных о том, что именно в то время могли вывозить Калхедон и Ольвия. Proxenes are an important source to study economical and trade interrelations of Olbia and other ancient poleis. The fragment of one of the last proxenes was found during the excavations of the Apollo Iethrosos temple on the western temenos of Olbia. It can be restored by the part of inscription which has been intact that the proxene had been granted for an inhabitant of Kalkhedon and his descendants who took not only proxene proper but also polity, atelia and free on duty import and export of articles both at peace-time and at war-time in the second half of the 4lh century BC. Judging by other sources in the 3rd century BC unknown inhabitant of Olbia took the proxene in Kalkhedon. This polis located near the narrow strait of the Thracean Bosporus took a great part in the trade occupation of Olbia inhabitants in their interrelations with Greek towns of Aegean Sea at the Hellenistic time. The authors deal with possible version of the trade interrelations of Olbia and Kalkhedon, so far as the proxenes don’t give concrete data about export of Kalkhedon and Olbia at this time.